Crucial Criteria Relevant to National Culture in Preserving Harmony Among Diverse Ethnicities - Hasnan, Siti Farhanah; Ramli, Razamin; Abdul Hamid, Mohd Noor (2022)
In a country with diverse ethnicities and different cultures, it is crucial to sustain the harmony among the people and nurture the spirit of unity in diversity. The ultimate aim of unity and harmony is to drive prosperous development of the country. Therefore, this paper examined the crucial criteria relevant to the national culture that are deemed most appropriate in contributing towards preserving the harmony in a nation with diverse ethnicities. Subsquently, this study utilized the qualitative expert judgment and the Rank Order Centroid (ROC) method to rank important criteria related to the national culture, wihich contribute towards the harmonious living in the context of Malaysia. The results revealed five crucial criteria in descending order are respecting elders, brotherhood, tolerance, mutual understanding and morality. It can he concluded that these criteria are the most effective in contributing towards a harmonious nation